Bismuth telluride inverse opal fabricated by colloidal templating with electrodeposition - Yap, Sabrina Hui Qing. (2009)
This project demonstrates that macroporous three-dimensional bismuth telluride (Bi2Te3) film with periodic submircron spherical holes arranged in a close-packed structure (inverse opal) can be fabricated via colloidal templating with electrodeposition. A synthetic opal structure host of polystyrene (PS) latex spheres of 400 nm diameter was first assembled on indium tin oxide (ITO) coated glass substrate. Bi2Te3 was subsequently infiltrated to the pores of PS opal by using electrochemical deposition. Three-dimensional Bi2Te3 inverse opal structure was obtained after removal of the PS opal template via heat treatment. Using an electrolyte solution of Bi/Te in volumetric proportion of 1:1 with concentration of 1.0 mM in an HNO3 acidic bath, Bi-rich and Te-rich Bi2Te3 inverse opals were obtained by changing the deposition current density from 0.1 mA/cm2 to 5 mA/cm2. A series of Bi-Te inverse opal samples have been characterized by field emission scanning electron microscopy, x-ray powder diffraction, energy dispersive x-ray spectroscopy and electrical resistivity test. The optimum current density to successfully infiltrate Bi2Te3 into the colloidal template is 2 mA/cm2 where three-dimensional Bi2Te3 inverse opal (>15 layers) with good stoichiometry was achieved.